Systematic review and meta‐analysis on the incidence and prevalence of autoimmune hepatitis in Asian, European, and American population. Issue 10 (7th July 2019) - Lv, Tingting; Li, Min; Zeng, Na; Zhang, Jingqi; Li, Shuxiang; Chen, Sha; Zhang, Chunpan; Shan, Shan; Duan, Weijia; Wang, Qianyi; Wu, Shanshan; You, Hong; et al.
Abstract: Background and Aim: Reported incidence and prevalence rates of autoimmune hepatitis (AIH) have been sparse and heterogeneous. The aim of this meta‐analysis was to estimate the worldwide incidence and prevalence rates of AIH and reveal population difference. Methods: Published articles on the epidemiology of AIH in PubMed, Embase, and Cochrane Library were systematically searched from inception to April 28, 2019. Two investigators independently reviewed these literatures and evaluated their quality. A random‐effects model was used to pool the overall incidence and prevalence rates. The impact of population difference, gender, age, study period, study quality, diagnostic criteria, and study design was further analyzed with subgroup analysis and meta‐regression. Results: A total of 22 studies were included in the meta‐analysis. The pooled worldwide annual incidence and prevalence of AIH were 1.37 (95% confidence interval [CI]: 0.95–1.80) and 17.44 (95% CI: 12.01–22.87) per 100 000 persons, respectively. Subgroup analysis showed that the pooled annual incidence for Asian, European, and American population was 1.31 (95% CI: 0.42–2.20), 1.37 (95% CI: 1.10–1.64), and 1.00 (95% CI: 0.44–1.56) per 100 000 persons, respectively; the pooled prevalence for Asian, European, and American population was 12.99 (95% CI: 2.05–23.92), 19.44 (95% CI: 15.63–23.24), and 22.80 (95% CI: −13.48 to 59.07) per 100 000 persons, respectively. In addition, higher incidence and prevalence rates were observed in women than men, and a higher prevalence rate was observed in elderly than young people. Conclusions: Autoimmune hepatitis is a rare disease, with a similar incidence worldwide and a higher prevalence in European and American than in Asian population.